Portfolio diversification - Lhabitant, Francois-Serge (Quantitative finance set., 2017)
"Portfolio Diversification provides an update on the practice of combining several risky investments in a portfolio with the goal of reducing the portfolio's overall risk. In this book, readers will find a comprehensive introduction and analysis of various dimensions of portfolio diversification (assets, maturities, industries, countries, etc.), along with time diversification strategies (long term vs. short term diversification) and diversification using other risk measures than variance. Several tools to quantify and implement optimal diversification are discussed and illustrated. Focuses on portfolio diversification across all its dimensionsIncludes recent empirical material that was created and developed specifically for this bookProvides several tools to quantify and implement optimal diversification."--Publisher description